Aligned carbon nanotube from catalytic chemical vapor deposition technique for energy storage device: a review - Mohd Abid, Mohd Asyadi Azam; Abdul Manaf, Nor Syafira; Bistamam, Mohd Shahril Amin; Talib, Elyas (Springer, 2013)
Carbon nanomaterial especially carbon nanotube (CNT) possesses remarkably significant achievements towards the development of sustainable energy storage applications. This article reviews aligned CNTs grown from chemical vapor deposition (CVD) technique as electrode material in batteries and electrochemical capacitors. As compared to the entangled CNTs, aligned or well organized CNTs have advantages in specific surface area and ion accessibility in which, more electrolyte ions can access to CNT surfaces for better charge storage performance. CVD known as the most popular technique to produce CNTs enables the use of various substrates and CNT can grow in a variety of forms, such as powder, films, aligned or entangled. Also, CVD is a simple and economic technique, and has good controllability of direction and CNT dimension. High purity of as-grown CNTs is also another beauty of the CVD technique. The current trend and performance of devices utilizing CNTs as electrode material is also extensively discussed.